MIRRORS OF THE PAST: REFLECTIONS OF HISTORY IN THE HISTORICAL PROSE OF WALTER SCOTT AND HILARY MANTEL - Nazarova, Raykhon (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The article is concerned with a comparative analysis of the works of two outstanding authors, each of whom has made their contribution to the genre of the historical novel. The research aims to highlight how Mantel and Scott approach the portrayal of historical events and figures, reflecting them through the lens of their own unique styles and historical interpretations. It also emphasizes that both writers utilize detailed historical accuracy as the foundation for their works, yet their methods of depicting characters and events differ. Walter Scott is known for his idealized and romanticized portrayal of the past, upholding national myths and striving to create an image of a polite nation. On the other hand, Hilary Mantel introduces a new level of psychological depth and moral complexity to the historical novel, presenting her characters in a more realistic and ambivalent light. The article analyzes differences in narrative structure, approaches to characters, and thematic emphases, focusing on how each author’s writing technique creates their unique view of the past. Particular attention is paid to how Mantel uses a complex narrative structure with multiple timelines and points of view, while Scott favors a more traditional and linear narrative. Concluding with a discussion on the influence of both authors’ works on modern historiography, the article provides a comprehensive look at how historical prose can simultaneously be a source of entertainment and a serious historical narrative. The result of the undertaken research not only identifies key commonalities and differences in the historical novels of Mantel and Scott but also emphasizes the timeless nature of the historical novel as a means to explore and understand the past.